2020
DOI: 10.1002/ps.6219
|View full text |Cite
|
Sign up to set email alerts
|

Review: evolutionary drivers of agricultural adaptation in Lolium spp.

Abstract: The genus Lolium comprises many species, of which L. perenne ssp. multiflorum, L. perenne ssp. perenne, and L. rigidum are of worldwide agricultural importance as both pasture crops and as weeds. These three species are inter‐fertile, obligate out‐crossers with a self‐incompatible reproduction system. This combination contributes to high genetic diversity that supplies new variants during expansion to new natural areas and agricultural environments. Human dispersal, de‐domestication and crop‐weed hybridization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…The research comparing the influence of the differing levels of soil disturbance and residue levels in minimum, no- and/or zero tillage systems on seedbank distribution and persistence is limited and inconclusive. Continuous cropping systems have been selected for higher dormancy in annual ryegrass populations compared to more disruptive systems with a pasture phase or break crops [ 28 ].…”
Section: Biology and Ecologymentioning
confidence: 99%
“…The research comparing the influence of the differing levels of soil disturbance and residue levels in minimum, no- and/or zero tillage systems on seedbank distribution and persistence is limited and inconclusive. Continuous cropping systems have been selected for higher dormancy in annual ryegrass populations compared to more disruptive systems with a pasture phase or break crops [ 28 ].…”
Section: Biology and Ecologymentioning
confidence: 99%
“…is the most economically damaging weed of southern Australian cropping systems and is also a major problem in parts of Africa, Europe and the Middle East. 1,2 In response to repeated and intensive use of selective post-emergence herbicides inhibiting acetyl-CoA carboxylase and acetolactate synthase, annual ryegrass populations have developed widespread resistance to these modes of action, and growers are returning to soil-applied pre-emergence herbicides to maintain adequate levels of weed control. 3 Inevitably, this has led to an increasing frequency of resistance to pre-emergence herbicides such as trifluralin (an inhibitor of microtubule assembly, mode of action group 3), and prosulfocarb, triallate and pyroxasulfone (inhibitors of very-long-chain fatty acid biosynthesis, group 15), [4][5][6] with most resistant populations exhibiting resistance to two or more of these herbicides.…”
Section: Introductionmentioning
confidence: 99%
“…This may also enable populations to adapt more rapidly to the management practices other crop production systems. 23 Our H E results indicate that the magnitude of D. insularis dispersion is greater than observed in the outcrossing weed species Alopecurus myosuroides , where it was found that H E varied from 0.09 to 0.14, approximately, in populations exhibiting different patterns of herbicide resistance. 24 Similarly, the H E value of D. insularis is larger than that of the predominantly self‐pollinated weed species Bromus tectorum which exhibited a mean H E of 0.2.…”
Section: Discussionmentioning
confidence: 48%